Etching of two-dimensional materials. (January 2021) - Sun, Haibin; Dong, Jichen; Liu, Fengning; Ding, Feng
Graphical abstract: Etching of two dimensional (2D) materials, being the reverse of the growth process, can help us to deeply understand the growth mechanism, identify point and line defects in a 2D material, improve the quality of 2D materials by combining the growth process, and fabricate the 2D heterojunctions. Thus, a comprehensive review of the etching behavior of 2D materials is a much-needed presentation, which includes the: (i) etching of single- and poly-crystal 2D materials; (ii) etching of multilayer 2D materials; (iii) experimental factors, such as partial pressure of H2, etchant species, and substrate, that affect 2D materials etching; (iv) applications of etching in graphene and other 2D materials synthesis, characterization and processing. Abstract: Etching is one of the key steps in materials processing in the semiconducting industry and recent progress in this field has shown that etching can be used to create various structures of two-dimensional (2D) materials, and can be viewed as a complementary technique to growth. Besides, etching has many other applications in 2D materials synthesis, processing and characterization, such as helping to understand the growth mechanism in-depth, identifying point and line defects in a 2D material, improving the quality of 2D materials by combining the growth process, and for fabricating 2D heterojunctions. Here, we review the current progress on the etching of graphene and other 2D materials; the content of this review includes: (i) etching of single-crystalline 2D materials; (ii) etching of multilayer 2D materials; (iii) etching of polycrystalline 2D materials; (iv) experimental factors, such as partial pressure of etchants, etchant species, and substrate, that affect 2D materials etching; (v) applications of etching in graphene and other 2D materials synthesis, characterization and processing and (vi) the challenges and opportunities in 2D materials etching.